Phosphatidylcholine Liposomes Down-Modulate CD4 Expression Reducing HIV Entry in Human Type-1 Macrophages - De Santis, Federica; Lopez, Ana Borrajo; Virtuoso, Sara; Poerio, Noemi; Saccomandi, Patrizia; Olimpieri, Tommaso; Duca, Leonardo; Henrici De Angelis, Lucia; Aquilano, Katia; D’Andrea, Marco Maria; Aquaro, Stefano; Borsetti, Alessandra; et al. (Frontiers in Immunology, 2022)
One of the strategies adopted to combat human immunodeﬁciency virus type-1 (HIV-1) infection is based on interfering with the virus entry into target cells. In the present study, we found that phosphatidylcholine (PC) liposomes reduced the expression of CD4 receptor in human primary type-1 macrophages, but not in CD4+ T cells. The down-regulation was specific for CD4, as any effect was not observed in CCR5 membrane expression. Moreover, the reduction of membrane CD4 expression required the Ca2+-independent protein kinase C (PKC), which in turn mediated serine phosphorylation in intracytoplasmic tail of the CD4 receptor. Serine phosphorylation of CD4 was also associated with its internalization and degradation in acidic compartments. Finally, the observed CD4 down-regulation induced by PC liposomes in human primary macrophages reduced the entry of both single cycle replication and replication competent R5 tropic HIV-1. Altogether, these results show that PC liposomes reduce HIV entry in human macrophages and may impact HIV pathogenesis by lowering viral reservoir.